Réponses

  • Utilisateur Brainly
2012-06-07T19:47:10+02:00

au collège....

7x^2+10x-6=0

7(x^2+(10/7)x-(6/7))=0

x^2+(10/7)x-(6/7)=0

c'est le début de (a+b)^2=a^2+2ab+b^2

x^2+(10/7)x-(6/7)=(x+(5/7))^2-(5/7)^2-(6/7)=0

(x+(5/7))^2-(25/49)-(42/49)=0

(x+(5/7))^2-(67/49)=0

 et on factorise en utilisant a^2-b^2=(a+b)(a-b)

(x+(5/7)-(√67/7)(x+(5/7)+(√67/7)=0

(x+(5-√67)/7)((x+(5+√67)/7)=0

un produit de facteurs est nul si l'un des facteurs est nul

x+(5-√67)/7=0==> x=(-5+√67)/7

x+(5+√67)/7=0 ==> x=(-5-√67)/7